Cutaneous bacteriological profile in patients with pemphigus - K C Kiran; J Madhukara; Anil Abraham; S Muralidharan (Wolters Kluwer Medknow Publications, 2018)
Background: Pemphigus is an autoimmune blistering disease. The common cause of death in pemphigus is septicemia which is usually secondary to cutaneous bacterial infection. Aim: The aim was to study the cutaneous bacteriological profile in patients with pemphigus. Materials and Methods: Pus for culture and sensitivity was collected from clinically infected lesions of pemphigus patients in the Department of Dermatology, St. John's Medical College Hospital, Bengaluru, from June 2013 to June 2014. Results: Of the 49 patients included in the study, 44 were suffering from pemphigus vulgaris, 4 from pemphigus foliaceus and one had pemphigus vegetans. There were 31 male and 18 female patients. The mean age of the group was 35.51 year. Mean Autoimmune Bullous Disorder Intensity Score was 17.36. About 32.7% were diabetic. About 40.81% showed the growth of Staphylococcus aureus, 12.24% of Pseudomonas aeruginosa, 6.12% of Proteus mirabilis, 4.08% of β-hemolytic streptococci and nonfermenting Gram-negative bacilli, and 2.04% of Proteus vulgaris, Staphylococcus saprophyticus, Enterococcus species, and Klebsiella species. S. aureus showed 100% sensitivity to antibiotics - tetracycline, amikacin, chloramphenicol, and netilmicin; 90% resistance was found for penicillin and 55% resistance was found for ciprofloxacin and erythromycin. Methicillin-resistant S. aureus was 30%. P. aeruginosa showed 100% sensitivity to ciprofloxacin, amikacin, gentamicin, piperacillin, piperacillin + tazobactam, and netilmicin. Conclusion: S. aureus was the most common organism showing sensitivity to tetracycline, amikacin, chloramphenicol, and netilmicin and resistance to penicillin, ciprofloxacin, and erythromycin.